Global Disparities in Road Safety: Trends, Knowledge Gaps, and Strategic Intervention - Setyowati, Dina Lusiana; Setyaningsih, Yuliani; Suryawati, Chiswardani; Lestantyo, Daru; Denny, Hanifa M; Kurniawan, Bina; Fauzi, Muhammad Ashraf; Siddiqui, Muhammad Ahsan (Universitas Airlangga, 2025)
Introduction: Traffic accidents remain a pressing global issue, disproportionately affecting low- and middle-income countries (LMICs) with higher mortality rates, socio-economic burdens, and persistent policy implementation challenges. This study conducts a bibliometric analysis to identify global trends, conceptual developments, and critical knowledge gaps in road safety research, with a focus on LMIC contexts. Methods: A total of 402 peer-reviewed journal articles published between 2014 and 2025 were retrieved from the Scopus database. Bibliometric coupling and co-word analysis were conducted using VOSviewer to explore research dynamics. Results: The analysis identified five thematic clusters: (1) gamification and technology integration, (2) behavioral insights and interventions, (3) risk perception and training, (4) equity and infrastructure design, and (5) cyclist crash risk mitigation. Global trends show increasing attention to digital tools such as virtual reality, machine learning, and simulation-based training. Conceptual developments include integrating behavioral science into traffic safety and designing inclusive infrastructure. However, critical gaps persist, particularly the limited representation of LMICs in the literature, lack of contextual adaptation, and minimal real-world validation of technological solutions. Conclusion: This study underscores the need for a multidimensional approach that unites technology, human behavior, and infrastructure improvements. Strengthening research in LMICs, validating emerging tools in real-life scenarios, and fostering cross-sectoral collaborations are key to reducing global traffic injuries and fatalities through evidence-informed policies.